Hypothalamic Obesity: 4 Years of the International Registry of Hypothalamic Obesity Disorders. Issue 11 (8th October 2018) - Rose, Susan R.; Horne, Vincent E.; Bingham, Nathan; Jenkins, Todd; Black, Jennifer; Inge, Thomas
Abstract : Objective: Hypothalamic obesity (HyOb) is a rare cause of rapid weight gain and early metabolic comorbidities. Effective treatment strategies are limited. The registry collected participant data and compared treatment approaches. Methods: The International Registry of Hypothalamic Obesity Disorders (IRHOD) was created as a registry portal to provide education. Data collected from the initial 4 years were evaluated. Results: Eighty‐seven participants were included for analysis (median age: 27 years, range: 3‐71 years). A total of 96.5% had obesity, and 3.5% had overweight at maximal weight. Seventy‐five had brain tumors (86%)—the majority were craniopharyngiomas (72% of those with tumors). Nontumor etiologies included congenital brain malformation (4.6%), traumatic brain injury (3.4%), and genetic anomaly (2.3%). Ninety percent received obesity treatments including nutritional counseling (82%), pharmacotherapy (59%), bariatric surgery (8%), and vagal nerve stimulation (1%). Forty‐six percent reported follow‐up BMI results after obesity treatment. Surgery was most effective (median BMI decrease: −8.2 kg/m 2, median interval: 2.6 years), with lifestyle intervention (BMI: −3.4 kg/m 2, interval: 1.2 years) and pharmacological therapy (BMI: −2.3 kg/m 2, interval: 0.8 years) being less effective. Eighty percent of participants reporting follow‐up weight remained in the obesity range. Conclusions: IRHOD identified a large cohort with self‐reported HyOb. Surgical therapy was most effective at weight reduction. Nutritional counseling and pharmacotherapy modestly improved BMI. Stepwise treatment strategy for HyOb (including nutritional, pharmacological, and surgical therapies in an experienced center) may be most valuable.